Foodborne Pathogen Screening Using Magneto-fluorescent Nanosensor: Rapid Detection of E. Coli O157:H7 - Shelby, Tyler (J Vis Exp, 2017)
Enterohemorrhagic Escherichia coli O157:H7 has been linked to both waterborne and foodborne illnesses, and remains a threat despite the food- and water-screening methods used currently. While conventional bacterial detection methods, such as polymerase chain reaction (PCR) and enzyme-linked immunosorbent assays (ELISA) can specifically detect pathogenic contaminants, they require extensive sample preparation and lengthy waiting periods. In addition, these practices demand sophisticated laboratory instruments and settings, and must be executed by trained professionals. Herein, a protocol is proposed for a simpler diagnostic technique that features the unique combination of magnetic and fluorescent parameters in a nanoparticle-based platform. The proposed multiparametric magneto-fluorescent nanosensors (MFnS) can detect E. coli O157:H7 contamination with as little as 1 colony-forming unit present in solution within less than 1 h. Furthermore, the ability of MFnS to remain highly functional in complex media such as milk and lake water has been verified. Additional specificity assays were also used to demonstrate the ability of MFnS to only detect the specific target bacteria, even in the presence of similar bacterial species. The pairing of magnetic and fluorescent modalities allows for the detection and quantification of pathogen contamination in a wide range of concentrations, exhibiting its high performance in both early- and late-stage contamination detection. The effectiveness, affordability, and portability of the MFnS make them an ideal candidate for point-of-care screening for bacterial contaminants in a wide range of settings, from aquatic reservoirs to commercially packaged foods.